Regulations Without Protection: State Failure in Safeguarding Passenger Rights - Sibatuara, Enjelina; Sudiro, Amad (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
Flight delays remain a persistent issue in Indonesia’s air transportation sector, directly impacting passengers through financial and non-material losses. This study aims to (1) analyze the legal responsibilities of air transportation business entities for flight delays under Law Number 1 of 2009, (2) evaluate the effectiveness of the compensation claim settlement mechanism in accordance with Law Number 8 of 1999 on Consumer Protection, and (3) uncover structural inequalities in the legal relationship between airlines and passengers. Employing a normative legal approach, the study draws upon both primary and secondary legal sources. The findings reveal that, despite an adequate regulatory framework, the enforcement of legal responsibilities and the functionality of claims mechanisms remain weak. A significant imbalance in bargaining power and access to justice persists between passengers and airlines, further exacerbated by ineffective state oversight. This study concludes that policy reform and a strengthened state supervisory role are essential to ensure legal certainty and the effective protection of passenger rights.